Urinary Eosinophil Protein X in Childhood Asthma: Relation with Changes in Disease Control and Eosinophilic Airway Inflammation - Nuijsink, Marianne; Hop, Wim C. J.; Sterk, Peter J.; Duiverman, Eric J.; De Jongste, Johan C. (Mediators of Inflammation, 2013)
The aim of this study was to assess cross-sectional and longitudinal correlations between uEPX and other markers of asthma control and eosinophilic airway inflammation. Methods. We measured uEPX at baseline, after 1 year and after 2 years in 205 atopic asthmatic children using inhaled fluticasone. At the same time points, we assessed symptom scores (2 weeks diary card), lung function (forced expiratory volume in one second (FEV1)), airway hyperresponsiveness (AHR), and percentage eosinophils in induced sputum (% eos). Results. We found negative correlations between uEPX and FEV1 at baseline (r=-0.18,P=0.01), after 1 year (r=-0.25,P<0.01) and after 2 years (r=-0.21,P=0.02). Within-patient changes of uEPX showed a negative association with FEV1 changes (at 1 year: r=-0.24,P=0.01; at 2 years: r=-0.21,P=0.03). Within-patient changes from baseline of uEPX correlated with changes in % eos. No relations were found between uEPX and symptoms. Conclusion. In this population of children with atopic asthma, uEPX correlated with FEV1 and % eos, and within-subjects changes in uEPX correlated with changes in FEV1 and % eos. As the associations were weak and the scatter of uEPX wide, it seems unlikely that uEPX will be useful as a biomarker for monitoring asthma control in the individual child.